2014
DOI: 10.1371/journal.pone.0105217
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimalarial Activity and Toxicity of a New Primaquine Prodrug

Abstract: Plasmodium vivax is the most prevalent of the five species causing malaria in humans. The current available treatment for P. vivax malaria is limited and unsatisfactory due to at least two drawbacks: the undesirable side effects of primaquine (PQ) and drug resistance to chloroquine. Phenylalanine-alanine-PQ (Phe-Ala-PQ) is a PQ prodrug with a more favorable pharmacokinetic profile compared to PQ. The toxicity of this prodrug was evaluated in in vitro assays using a human hepatoma cell line (HepG2), a monkey ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…); (iii) incubation time (30 min (Hollmann et al 2016;Wu et al 2014), 1 hour (Chongsiriwatana et al 2008;Dennison and Phoenix 2014;Yang et al 2013), 4 hrs (Li et al 2005) or 18-24 hrs (Mojsoska et al 2015)); (iii) used positive control (0.1% Triton-X (Dennison and Phoenix 2014;Lee and Lee 2008;Song et al 2005), 1% Triton-X (Mojsoska et al 2015), 10% Triton-X (Wu et al 2014), distilled water (Hollmann et al 2016;Yang et al 2013), 2 % SDS (Zeitler et al 2013), 0.05% saponin (Davanco et al 2014). There are differences even in the used wavelength at which the optical density of released haemoglobin is determined (λ=350 nm (Chongsiriwatana et al 2008), 405-415 nm (Kaushik et al 2012;Lee and Lee 2008;Song et al 2005;Zeitler et al 2013) , 540-550 nm (Davanco et al 2014;Hollmann et al 2016;Mojsoska et al 2015;Yang et al 2013) or 570 nm (Dennison and Phoenix 2014;Wu et al 2014)). …”
Section: Experimental Conditions Of In Vitro Assaysmentioning
confidence: 99%
“…); (iii) incubation time (30 min (Hollmann et al 2016;Wu et al 2014), 1 hour (Chongsiriwatana et al 2008;Dennison and Phoenix 2014;Yang et al 2013), 4 hrs (Li et al 2005) or 18-24 hrs (Mojsoska et al 2015)); (iii) used positive control (0.1% Triton-X (Dennison and Phoenix 2014;Lee and Lee 2008;Song et al 2005), 1% Triton-X (Mojsoska et al 2015), 10% Triton-X (Wu et al 2014), distilled water (Hollmann et al 2016;Yang et al 2013), 2 % SDS (Zeitler et al 2013), 0.05% saponin (Davanco et al 2014). There are differences even in the used wavelength at which the optical density of released haemoglobin is determined (λ=350 nm (Chongsiriwatana et al 2008), 405-415 nm (Kaushik et al 2012;Lee and Lee 2008;Song et al 2005;Zeitler et al 2013) , 540-550 nm (Davanco et al 2014;Hollmann et al 2016;Mojsoska et al 2015;Yang et al 2013) or 570 nm (Dennison and Phoenix 2014;Wu et al 2014)). …”
Section: Experimental Conditions Of In Vitro Assaysmentioning
confidence: 99%
“…However, it has hemolytic effects, especially in people with glucose-6-phosphate dehydrogenase deficiency (G6PD), in which primaquine as a stressor to the erythrocyte induces hemolysis. Hemolysis induced by primaquine can result in discoloration of urine and faeces and it is dose related [ 8 , 9 ]. Gastrointestinal disorders, such as nausea, dizziness, and vomiting, are common but usually not present as severe complications, especially when primaquine is administered with food.…”
Section: Introductionmentioning
confidence: 99%
“…The naphthoquinone derivatives are toxic and several studies have shown that the structure changes in the molecule have reduced its cytotoxic effect, and improve biological activity. Davanço et al [9] , evaluated a prodrug primaquine and when compared with the primaquine, it was less cytotoxic to BGM and HepG2 cells, caused less hemolysis of G6PD deficient red blood cells and caused less alteration in the biochemical parameters. In their study Oliveira et al [31] produced a derivative of vanillin molecule from its condensation with resorcinol and absence of cytotoxicity observed in murine macrophage cells derived compound, while the vanillin presented an IC50 of 645 μg/mL.…”
Section: Discussionmentioning
confidence: 99%